(De)pathologizing of life: perspectives of social workers in Recôncavo of Bahia - Magalhães, Vinicius Pinheiro de; Santos, Vera Núbia (Argumentum, 2020)
This work was guided by the purpose of analyzing the conception of Social Service professionals about the madness and treatment of users of the Psychosocial Care Centers (Centros de Atenção Psicossocial [CAPS]) and the relationship between their considerations and the professional Ethical-Political Project (EPP). The research had an empirical nature and a qualitative approach. Interviews were carried out with five social workers of CAPS I from the municipalities of Recôncavo Baiano and content analysis by thematic categorization was used. The considerations of social workers were outlined in a psychosocial perspective, as they dialogue with both biological and pathological assumptions, and with the dimension of citizenship. It is highlighted, therefore, the need for this professional category to establish more organic relations with the social movements linked to the Anti-Asylum Fight, which act in an essentially de-pathologizing perspective of life.